Transformasi Kurikulum Pendidikan Artificial Intelligence di Era Society 5.0 - Harjun Harjun; Juwantho Lewa; Wahyu Muh Syata; WD. ST. Febri Wardamianingsih (CV. Rumoh Aceh Publishing, 2026)
This study analyzes the transformation of the Artificial Intelligence (AI) Education Curriculum in the Society 5.0 Era. This study uses the Systematic Literature Review (SLR) method as the primary approach to examine the development, patterns, and direction of the transformation of the Artificial Intelligence (AI) education curriculum in the Society 5.0 era. Based on the results of the literature review on the transformation of the Artificial Intelligence (AI)-based curriculum in the Society 5.0 era, it shows that the current curriculum development demands the integration of technology, 21st-century skills, and character values. The curriculum no longer focuses on knowledge transfer but also on developing critical thinking, creativity, collaboration, and digital literacy skills in students. The implementation of the Independent Curriculum is a relevant form of adaptation in addressing these challenges, as it provides a student-centered learning platform and encourages the use of technology.